A Case of Good Efficacy of Tolvaptan in a Patient with Markedly Enlarged Polycystic Kidney - Mizuta, Masato; Suwabe, Tatsuya; Sekine, Akinari; Yamanouchi, Masayuki; Mizuno, Hiroki; Ikuma, Daisuke; Hasegawa, Eiko; Oba, Yuki; Inoue, Noriko; Fukuda, Makoto; et al. (Journal of Clinical Nephrology, 2024)
A 61-year-old patient with autosomal dominant polycystic kidney disease (Irazabal class 1E) in whom renal function had decreased and kidney size had increased over the past 3 years (change in serum creatinine, 1.3 mg/dL to 1.5 mg/dL; change in total kidney volume, 5632 cm3 to 7301 cm3) was treated with tolvaptan 60 mg/day. After 8 years of tolvaptan treatment, serum creatinine remained at 1.51 mg/dL, and total kidney volume was at 6812 cm3. Adequate salt intake and good weight control may have resulted in good outcomes, even in patients with treatment-resistant giant cystic kidney disease.